Optimal nitrogen fertilizer, which determines straw properties, and pyrolysis temperatures produce desired-biochars that can be used as a soil amendment. (December 2022) - Zhang, Jining; Zhang, Xianxian; Wang, Cong; Sun, Huifeng; Zhou, Sheng
Abstract: This study investigated the straw harvested after nitrogen (N) fertilizer application levels (0, 75, 150 and 225 kg N hm −2 ). The N fertilizer increased straw yield by 115.4–190.6%. In addition to N fertility, the pyrolysis temperatures (300, 500 and 700 °C) induced significant changes of the straw-derived biochar samples. The yield reduced from 41.4 wt% to 23.2 wt%, the residence time increased from 272 yr to 2194 yr, and the residual coefficient of organic C ( F p e r m ) increased from 0.65 to 0.93 for the biochar samples as the temperature rising. The parameters of C sequestration were mainly affected by pyrolysis temperature. The N + P2 O5 +K2 O content (5.6–8.8%) of the biochar samples was more in the 500 °C treatment. The characteristics of nutrient supply were affected by both the N fertility and pyrolysis temperature. The N fertilizer rate of 150 kg N hm −2 in the soil for wheat straw, together with the 500 °C treatment induces the best nutrient donor and C sequestration after biochar incorporation into the soil. Graphical abstract: Image 1 Highlights: Nitrogen fertilizer rate at 150 kg N hm −2 produces nutrient-rich straw. Nitrogen fertilizer and pyrolysis temperatures produce desired straw biochars. Highest N + P2 O5 +K2 O content occurred in the 500 °C biochar treatment. The MRT of 1151–1294 yr calculated in the 500 °C biochar samples.